RETHINKING PERAN PEREMPUAN DALAM KELUARGA - Mariatul Qibtiyah Harun AR (Karsa: Journal of Social and Islamic Culture, 2015)
It has been an urgent agenda to rediscuss the women role in regards to classic assumption proclaimed that women deserve to be in the house and manage domestic matters. Therefore, the questions would be: will it be a gender problem and a kind of descrimination if women stay at home at all times? What if the women prefer staying at home, as convinient and comfortable choice, to having career freely in public sphere? By keeping up the construction of role sharing with the absence of negotiation and reconsideration about role and position of men and women in a family, might facilitate the strength of gender imbalance that can inflict the both sides.Copyright (c) 2015 by KARSA. All right reservedDOI: 10.19105/karsa.v23i1.607